Knowledge collaboration between organizations and online communities: the role of open innovation intermediaries. Issue 6 (9th October 2017) - Randhawa, Krithika; Josserand, Emmanuel; Schweitzer, Jochen; Logue, Danielle
Abstract : Purpose: This research paper aims to examine how open innovation (OI) intermediaries facilitate knowledge collaboration between organizations and online user communities. Drawing on a Community of Practice (CoP) perspective on knowledge, the study lays out a framework of the knowledge boundary management mechanisms (and associated practices) that intermediaries deploy in enabling client organizations to engage in online community-based OI. Design/methodology/approach: This research is based on an exploratory case study of an OI intermediary and 18 client organizations that engage with online user communities on the intermediary's platform. Results incorporate both the intermediary and clients' perspective, based on analysis of intermediary and client interviews, clients' online community projects and other archival data. Findings: Results reveal that OI intermediaries deploy three knowledge boundary management mechanisms – syntactic, semantic and pragmatic – each underpinned by a set of practices. Together, these mechanisms enable knowledge transfer, translation and transformation, respectively, and thus lead to cumulatively richer knowledge collaboration outcomes at the organization–community boundary. The findings show that the pragmatic mechanism reinforces both semantic and syntactic mechanisms, and is hence the most critical to achieving effective knowledge collaboration in community-based OI settings. Practical implications: The findings suggest that OI intermediaries have to implement all three boundary management mechanisms to successfully enable knowledge collaboration for community-based OI. More specifically, intermediaries need to expand their focus beyond the development of digital platforms, to include nuanced efforts at building organizational commitment to community engagement. Originality/value: Drawing on the CoP view, this study integrates the knowledge management literature into the OI literature to conceptualize the role of OI intermediaries in shaping knowledge collaboration between organizations and communities. In engaging with the interactive nature of knowledge exchange in such multi-actor settings, this research extends the firm-centric theorization of knowledge that currently dominates the existing OI research.